Recovery of Ammonical Salts from Mother Liquid of 2-Methyl-5-nitroimidazole - DONGARE, M.K.; RODE, C.V.; CHANDORKAR, J.G. (Asian Journal of Chemistry, 2010)
An attempt have been made to recover the ammonical salt (ammonium sulphate and ammonium nitrate) from the mother liquid of 2-methyl-5-nitroimidazole successfully.